2012
DOI: 10.1016/j.ygcen.2011.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Sex and species differences in plasma testosterone and in counts of androgen receptor-positive cells in key brain regions of Sceloporus lizard species that differ in aggression

Abstract: We studied neuroendocrine correlates of aggression differences in adults of two Sceloporus lizard species. These species differ in the degree of sex difference in aggressive color signals (belly patches) and in aggression: S. undulatus (males blue, high aggression; females white, low aggression) and S. virgatus (both sexes white, lower aggression). We measured plasma testosterone and counted cells expressing androgen receptor-like immunoreactivity to the affinity-purified polyclonal AR antibody, PG-21, in thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 72 publications
2
19
0
Order By: Relevance
“…Plasma androgens did not differ between male and female E. quoyii, although there was substantial variation within each sex. A lack of androgen differences between the sexes has been observed in other taxa (Ketterson et al, 2005), including lizards (Hews et al, 2012). Ketterson et al (2005), provides evidence that testosterone is higher in females of sexually monomorphic bird species, and, although the data in lizards are limited, comparisons between two Sceloporus species that differ in female aggression and degree of sexual dimorphism have revealed similar findings (Hews et al, 2012).…”
Section: Discussionmentioning
confidence: 67%
“…Plasma androgens did not differ between male and female E. quoyii, although there was substantial variation within each sex. A lack of androgen differences between the sexes has been observed in other taxa (Ketterson et al, 2005), including lizards (Hews et al, 2012). Ketterson et al (2005), provides evidence that testosterone is higher in females of sexually monomorphic bird species, and, although the data in lizards are limited, comparisons between two Sceloporus species that differ in female aggression and degree of sexual dimorphism have revealed similar findings (Hews et al, 2012).…”
Section: Discussionmentioning
confidence: 67%
“…In a pairwise comparison between two sister species of voles ( Microtus ) in which one species is monogamous and the other is promiscuous, the MPON was sexually dimorphic only in the species under strong sexual selection (Shapiro et al ., ). In a similar comparison between two fence lizards ( Sceloporus ), only the species under strong sexual selection had sexually dimorphic aromatase‐expressing cell counts in the MPON and VMN (Hews et al ., ). Based on these studies, we propose that strong sexual selection increases sexual dimorphism in brain regions that control sexual activity, as these regions have a direct impact on reproductive success, the ultimate target of sexual selection.…”
Section: Introductionmentioning
confidence: 99%
“…In S. undulatus, sex differences in growth and color development between males and females are likely through sex differences in circulating androgen levels, similar to what occurs in A. sagrei, but sexual dimorphisms may also arise in part through sex differences in androgen-receptor densities. Hews et al (2012) and Moga et al (2000), for example, reported that while both male and female S. undulatus had androgen receptors present in regions of the brain, males had higher receptor densities and higher circulating testosterone than their female counterparts.…”
Section: Growthmentioning
confidence: 99%